Quantum Defects as a Toolbox for the Covalent Functionalization of Carbon Nanotubes with Peptides and Proteins. Issue 40 (13th July 2020) - Mann, Florian A.; Herrmann, Niklas; Opazo, Felipe; Kruss, Sebastian
Abstract: Single‐walled carbon nanotubes (SWCNTs) are a 1D nanomaterial that shows fluorescence in the near‐infrared (NIR, >800 nm). In the past, covalent chemistry was less explored to functionalize SWCNTs as it impairs NIR emission. However, certain sp 3 defects (quantum defects) in the carbon lattice have emerged that preserve NIR fluorescence and even introduce a new, red‐shifted emission peak. Here, we report on quantum defects, introduced using light‐driven diazonium chemistry, that serve as anchor points for peptides and proteins. We show that maleimide anchors allow conjugation of cysteine‐containing proteins such as a GFP‐binding nanobody. In addition, an Fmoc‐protected phenylalanine defect serves as a starting point for conjugation of visible fluorophores to create multicolor SWCNTs and in situ peptide synthesis directly on the nanotube. Therefore, these quantum defects are a versatile platform to tailor both the nanotube's photophysical properties as well as their surface chemistry. Abstract : Two new quantum defects were incorporated into single‐walled carbon nanotubes (SWCNT) carrying anchor groups for functionalization with biomolecules. The potential and versatility of this approach was demonstrated by the conjugation of a GFP‐binding nanobody as well as the growth of (fluorescent) peptide chains directly on the nanotube's carbon lattice.